Can I have my coffee and drink it? A systemtic review and meta-analysis to determine wether habitual caffeine consumption affects the ergogenic effect of caffeine - Carvalho, A.; Marticorena, F.M.; Grecco, B.H.; Barreto, G.; Saunders, B. (Sports Medicine, 2022)
Objective: The aim was to quantify the proportion of the literature on caffeine supplementation that reports habitual caffeine consumption, and determine the influence of habitual consumption on the acute exercise response to caffeine supplementation, using a systematic review and meta-analytic approach. Methods: Three databases were searched, and articles screened according to inclusion/exclusion criteria. Three-level meta-analyses and meta-regression models were used to investigate the influence of habitual caffeine consumption on caffeine`s overall ergogenic effect and within different exercise types (endurance, power, strength), in men and women, and in trained and untrained individuals. Sub-analyses were performed according to the following: acute relative dose (< 3, 3-6, > 6 mg/kg body mass [BM]); whether the acute caffeine dose provided was lower or higher than the mean daily caffeine dose; and the caffeine withdrawal period prior to the intervention (< 24, 24-48, > 48 h). Results: Sixty caffeine studies included sufficient information on habitual consumption to be included in the meta-analysis. A positive overall effect of caffeine was shown in comparison to placebo (standard mean difference [SMD] = 0.25, 95% confidence interval [CI] 0.20-0.30; p < 0.001) with no influence of relative habitual caffeine consumption (p = 0.59). Subgroup analyses showed a significant ergogenic effect when the caffeine dose was < 3 mg/kg BM (SMD = 0.26, 95% CI 0.12-0.40; p = 0.003) and 3-6 mg/kg BM (SMD = 0.26, 95% CI 0.21-0.32; p < 0.0001), but not > 6 mg/kg BM (SMD = 0.11, 95% CI - 0.07 to 0.30; p = 0.23); when the dose was both higher (SMD = 0.26, 95% CI 0.20-0.31; p < 0.001) and lower (SMD = 0.21, 95% CI 0.06-0.36; p = 0.006) than the habitual caffeine dose; and when withdrawal was < 24 h, 24-48 h, and > 48 h. Caffeine was effective for endurance, power, and strength exercise, with no influence (all p = 0.23) of relative habitual caffeine consumption within exercise types. Habitual caffeine consumption did not modify the ergogenic effect of caffeine in male, female, trained or untrained individuals. Conclusion: Habitual caffeine consumption does not appear to influence the acute ergogenic effect of caffeine.